A new species of the hermit crab genus Areopaguristes Rahayu & McLaughlin, 2010 (Crustacea: Decapoda: Anomura: Diogenidae) discovered in the Mesoamerican Barrier Reef of Belize, Caribbean Sea - Lemaitre, Rafael; Felder, Darryl L. (Zootaxa, 2012)
A new species of hermit crab, Areopaguristes tudgei, family Diogenidae, is fully described and illustrated, including acolor photograph. A dense population of this new species was discovered living intertidally in a concealed habitat undercoral boulders covered with calcareous algae, on the crest to fore-reef zone in Carrie Bow Cay, a small island located onthe western Caribbean Mesoamerican Barrier Reef of Belize. This new species, the 24rd of Areopaguristes Rahayu &McLaughlin, 2010, and fourth known in this genus from the western Atlantic, is superficially similar to those of thePaguristes tortugae complex. As in species of that complex, A. tudgei n. sp. has dense plumose setation on the chelipeds,and at least in females, a fringe of plumose setae on the dorsolateral margins of the chelae, and on the dorsal margins ofthe walking legs. The presence in A. tudgei n. sp. of this setal arrangement, previously considered the only definingcharacter of the P. tortugae complex, can be attributed to convergence. The new species is contrasted with all other westernAtlantic congeners, and a key is presented to aid in their identification. A list of all western Atlantic species of Paguristes sensu lato and their current generic assignments is included.